The dual roles of DNA-PKcs, NBS1, and TRF2 proteins in DNA repair and telomere end-capping - Williams, Eli Stowe, author; Ullrich, Robert L., advisor; Bailey, Susan M., committee member; Bedford, Joel S., committee member; Cornforth, Michael N., committee member; Ranu, Rajinder S., committee member (Colorado State University. Libraries, 2007)
Telomeres are the nucleoprotein structures located at the ends of linear chromosomes that distinguish naturally occurring chromosome ends from DNA double-strand breaks (DSBs). The ability to properly distinguish telomeres as such is critical to long term cellular survival as failure to do so can result in genomic instability and favor the progression towards cancer, cellular senescence or apoptosis. Cells unable to efficiently cap their chromosome ends are recognized cytogenetically as dicentric chromosomes which maintain telomere sequence at the point of fusion (telomere fusions). It has been shown that deficiencies in Telomere Repeat Binding Factor 2 (TRF2), a telomere binding protein, results in massive telomere dysfunction characterized by high numbers of telomere fusions, thus establishing TRF2 as an essential telomere end-capping protein. Surprisingly, TRF2 is rapidly and abundantly recruited to laser microbeam-induced damage, implicating this telomere protein in the early cellular response to DNA damage. We demonstrate that TRF2 is, in fact, not recruited to localized IR- or UV-induced DNA damage, arguing against a role for TRF2 in the DNA damage response, as well as illustrating important differences between damage produced by laser microbeams, as compared to other types of radiation. An abundance of evidence, however, confirms significant overlap between DNA repair proteins and telomeres. Most strikingly, deficiencies of key proteins involved in the cellular response to DNA damage, particularly the catalytic subunit of the DNA dependent protein kinase (DNA-PKcs), also lead to the formation of telomere fusions, suggesting a role for these proteins in telomere end-capping. We show here that auto-phosphorylation of DNA-PKcs is critical for its function at telomeres, as well as establish the utility of the BALB/c mouse in investigating the contribution of telomere dysfunction in driving genomic instability. NBS1, a homologous recombination (HR) protein critical in the cell's initial response to damage, has also been implicated in telomere end-capping. We demonstrate that cells depleted of NBS1 show an increase in telomere associations. Overall, this study helps to further clarify the complex interplay between DNA repair proteins and telomeres.
Missing page 97 in number only; text follows.
Keywords: molecular biology; cellular biology